Preparation method and application of high-strength and high-plasticity Zn-Mn alloy with core-shell structure

CN118028659BActive Publication Date: 2026-10-20UNIV OF SCI & TECH BEIJING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410120663.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-29
Publication Date
2026-10-20
Estimated Expiration
2044-01-29

AI Technical Summary

Technical Problem

已有文献中没有关于由Zn相,MnZn13相和MnZn9相这三种相构成的材料的报道

Benefits of technology

[0027]1.兼具高强度和高塑性。本发明铸态Zn-Mn合金的压缩应变大于50%不断裂,直至达到80%压缩应变仍然不断裂,此时压缩应力超过2300MPa,试样压扁,不得不终止测试。作为对比,金属间化合物相的体积分数超过60%的材料,压缩应变通常不超过10%。本发明Zn-Mn合金板材和棒材的强度高、塑性好。作为对比,已报道的Zn-Mn二元合金不能在伸长率大于10%的条件下,达到屈服强度大于250MPa且同时抗拉强度大于300MPa。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118028659B_ABST
    Figure CN118028659B_ABST
Patent Text Reader

Abstract

This invention belongs to the field of zinc alloys and their preparation and processing, and relates to a method for preparing and applying a high-strength, high-ductility Zn-Mn alloy with a core-shell structure. The Zn-Mn alloy material is composed of Mn and Zn... 13 It is composed of three phases: MnZn9 and Zn, among which MnZn 13 The volume fraction of MnZn9 is ≥60%, and MnZn is the dominant component. 13 The alloy of this invention has a core / shell structure with MnZn9 as the core and Mn / Zn9 as the shell, dispersed in the Zn phase. The alloy is prepared using casting technology with a cooling rate exceeding 750 K / min. In the as-cast state, it exhibits excellent plasticity, showing no cracks at compressive strain greater than 50% and no fracture at compressive strain reaching 80%. It can be rolled into plates and extruded into bars. The plates and bars have a yield strength greater than 250 MPa, a tensile strength greater than 300 MPa, and an elongation greater than 10%. They are biodegradable and possess good antibacterial and wear-resistant properties, making them suitable for manufacturing oil extraction tools, automotive parts, and products such as bone nails and plates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of zinc alloys and their preparation and processing, and relates to a method for preparing and applying a high-strength and high-ductility Zn-Mn alloy with a core-shell structure. Technical Background

[0002] Pure zinc has advantages such as biodegradability and antibacterial properties, but it has low hardness and strength, and poor wear resistance. At room temperature, pure zinc has a hardness of 32 HV, a yield strength of 17 MPa, a tensile strength of 30 MPa, and an elongation of 2% (see reference 1). Adding alloying elements is an effective method to improve the mechanical properties of pure zinc. The intermetallic compounds formed by alloying elements and Zn have a much higher hardness than Zn, which can hinder the movement of deformation modes in Zn, thereby significantly improving the hardness and strength of zinc alloys. With the increase of the amount of alloying elements added, the volume fraction of the intermetallic compound also increases, and the hardness of the alloy increases. However, because the plastic deformation capacity of the intermetallic compound is much lower than that of Zn, the plastic deformation capacity of the zinc alloy decreases significantly, until it loses its processability, i.e., there is a problem of inverse relationship between strength and hardness and plasticity.

[0003] Therefore, to ensure processability and prevent premature failure during use, the volume fraction of intermetallic compounds in zinc alloys is generally controlled to be less than 30%. Taking Zn-Mn alloys as an example, Mn combines with Zn to form the intermetallic compound MnZn. 13 See reference 2. In the reported high-ductility Zn-Mn binary alloys, the mass fraction of Mn does not exceed 1%, corresponding to MnZn 13 The volume fraction of Mn does not exceed 20%, and the hardness is below 75 HV (see reference 3). According to the Zn-Mn binary phase diagram (see reference 4), under thermodynamic equilibrium conditions, the MnZn9 phase can only be formed after the mass fraction of Mn exceeds 7.5%, and at this point the material will be entirely composed of MnZn. 13 It consists of the Zn and MnZn9 phases, but not the Zn phase. Existing literature does not contain any information about a Zn phase, MnZn9 phase, or a Zn9 phase. 13 Reports on materials composed of the three phases: Mn, Zn, and 9.

[0004] Existing technical documents

[0005] Document 1: Liu Z, Li R, Jiang R, et al. Effects of Al addition on the structure and mechanical properties of Zn alloys. Journal of Alloys and Compounds. 2016; 687:885-892.

[0006] Document 2: Shi ZZ, Li XM, Yao SL, et al. 300MPa grade biodegradable high-strength ductile low-alloy (BHSDLA) Zn-Mn-Mg alloys: An in vitro study. Journal of Materials Science & Technology. 2023; 138: 233-244.

[0007] Document 3: Sun J, Zhang X, Shi ZZ, et al. Adjusting comprehensive properties of biodegradable Zn-Mn alloy through solution heat-treatment, Materials TodayCommunications 2020; 23:101150.

[0008] Document 4: Shi ZZ, Yu J, Liu XF.Microalloyed Zn-Mn alloys: From extremely brittle to extraordinarily ductile at room temperature. Materials&Design.2018;144:343-352. Summary of the Invention

[0009] This invention discloses a high-strength and high-ductility Zn-Mn alloy with a core-shell structure, its preparation method and applications, and the specific technical solution is as follows;

[0010] A method for preparing a high-strength, high-ductility Zn-Mn alloy with a core-shell structure is characterized by using pure Zn and pure Mn as raw materials, with Mn comprising 4.0–5.7% by mass and the balance being Zn. The prepared raw materials are heated and melted in a graphite crucible. The melt is held at 500–600°C for 5–10 minutes and then poured into a mold made of a material with low thermal conductivity for cooling. The bottom of the mold is a base plate made of a material with high thermal conductivity, which is continuously cooled by a liquid at a temperature below 20°C. After entering the mold, the melt directly contacts the base plate and is rapidly cooled at a cooling rate greater than 750 K / min. After complete solidification, the Zn-Mn alloy is obtained, referred to as the as-cast Zn-Mn alloy. The as-cast Zn-Mn alloy is composed of Mn and Zn... 13 It is composed of three phases: MnZn9 and Zn, among which MnZn 13Together with MnZn9, they are collectively referred to as Zn-Mn intermetallic compounds.

[0011] MnZn 13 The principle behind the formation of the three-phase microstructure of MnZn9 and Zn is that high-speed cooling at a rate greater than 750 K / min results in a non-equilibrium microstructure. When the Mn content is less than 4.0%, the melt cooling rate produced by the aforementioned preparation method is insufficient to generate a sufficient non-equilibrium offset, preventing the formation of the MnZn9 phase. Furthermore, when the Mn content is greater than 5.7%, the volume fraction of the Zn phase in the Zn-Mn alloy is too low, potentially even dropping to 0%, leading to poor plasticity and workability of the alloy.

[0012] Furthermore, the material with low thermal conductivity is alumina, zirconium oxide, etc.; the material with high thermal conductivity is pure copper, pure silver, aluminum alloy, AlN, graphite, etc.; and the liquid is water, ethanol, etc.

[0013] Furthermore, the volume fraction of the Zn-Mn intermetallic compound phase is ≥60%, and the volume fraction of the Zn phase is 10% to 40%.

[0014] Furthermore, the MnZn 13 It forms a Zn-Mn core / shell structure with MnZn9, where the core is MnZn9 and the shell is MnZn. 13 This Zn-Mn core / shell structure is granular with an average size ≤40μm. The formation principle of this core-shell structure is as follows: during rapid cooling, MnZn9 first nucleates and grows, then the Mn content in the melt decreases, and MnZn... 13 Growth was achieved using MnZn9 as a heterogeneous nucleation site.

[0015] Furthermore, in the Zn-Mn core / shell structure, MnZn 13 The shell has a closed or open structure.

[0016] Furthermore, a Zn phase is continuously distributed between the Zn-Mn core / shell structured particles (see...). Figure 1 The principle behind this structure is that high-speed cooling at speeds greater than 750 K / min significantly increases the nucleation rate of Zn-Mn intermetallic compounds while limiting their growth rate.

[0017] Furthermore, the as-cast Zn-Mn alloy material can be plastically formed by rolling or extrusion to produce plates and bars of various sizes; the rolling process is: room temperature to 380°C, with a single-pass reduction rate of 5% to 40%; the extrusion process is: 200 to 350°C, with an extrusion ratio of 8:1 to 100:1; the resulting plates and bars have no surface cracks and good machinability. (See...) Figure 2 )

[0018] Furthermore, the as-cast Zn-Mn alloy possesses the following properties:

[0019] (1) The room temperature compressive mechanical properties are a yield strength greater than 230 MPa and no cracking when the strain is greater than 50%, exhibiting very high plasticity; (e.g.) Figure 3 (As shown)

[0020] (2) Hardness greater than 120HV;

[0021] (3) In an aqueous solution containing 3% KCl at 93℃, the weight loss rate is greater than 0.08 mg / (cm³). 2 ·h);

[0022] (4) In an aqueous solution containing 3% KCl at 93℃, a wear ball made of zirconia ceramic with a diameter of 10 mm was used to apply a force of 5 N and wear at a frequency of 60 Hz for 1 h, and the wear depth was less than 4 μm.

[0023] (5) It has antibacterial properties, with antibacterial rates of ≥85% against Staphylococcus aureus and Escherichia coli.

[0024] Furthermore, the room temperature tensile mechanical properties of the Zn-Mn alloy plates and bars are as follows: yield strength greater than 250 MPa, tensile strength greater than 300 MPa, and elongation greater than 10%; they have good anti-aging ability, and after being placed at room temperature for 1 year, the strength change is within 5%, with no significant difference.

[0025] The Zn-Mn alloy prepared according to the method described in this invention can be used to manufacture oil extraction tools such as soluble bridge plugs, automotive parts such as airbag housings and windshield wipers, as well as other products such as stove valve bodies, roller skate brackets, hardware handrails, medical equipment housings, bone nails, and bone plates.

[0026] The Zn-Mn alloy of this invention has the following advantages:

[0027] 1. Combining high strength and high ductility. The as-cast Zn-Mn alloy of this invention does not fracture at compressive strain greater than 50%, and even at 80% compressive strain, it still does not fracture. At this point, the compressive stress exceeds 2300 MPa, the sample flattens, and the test must be terminated. In contrast, materials with an intermetallic compound phase volume fraction exceeding 60% typically exhibit compressive strain not exceeding 10%. The Zn-Mn alloy plates and bars of this invention possess high strength and good ductility. In contrast, previously reported Zn-Mn binary alloys cannot achieve a yield strength greater than 250 MPa and a tensile strength greater than 300 MPa simultaneously under conditions where the elongation is greater than 10%.

[0028] 2. It possesses high hardness and high wear resistance. The as-cast Zn-Mn alloy of this invention has a hardness greater than 120HV, which is at least 1.5 times the hardness of existing Zn-Mn binary alloys; its wear resistance is at least twice that of pure zinc.

[0029] 3. Excellent plasticity and formability. The as-cast Zn-Mn alloy of this invention can be rolled and extruded. In contrast, materials with an intermetallic compound phase volume fraction exceeding 60% are easily broken during rolling and extrusion.

[0030] 4. It is biodegradable and has antibacterial properties. The as-cast Zn-Mn alloy of this invention degrades faster than pure zinc, with a weight loss rate greater than 0.08 mg / (cm³) in an aqueous solution containing 3% KCl at 93°C. 2 •h); Antibacterial activity against Staphylococcus aureus and Escherichia coli is ≥85%. Attached Figure Description

[0031] Figure 1 Metallographic diagram of Zn-Mn core / shell structured particles.

[0032] Figure 2 This is a scanning electron microscope image of Zn-Mn core / shell structured particles after 50% compression deformation.

[0033] Figure 3 The image shows the compressive stress-strain curve of the Zn-Mn alloy in Example 1. Detailed Implementation

[0034] The present invention will be further illustrated below with examples and comparative examples. These examples are only for explaining the present invention and are not intended to limit the present invention. The implementation can be modified without changing the essential points.

[0035] Example 1: A ductile Zn-Mn alloy with a core-shell structure volume fraction of 77%

[0036] Using pure Zn and pure Mn as raw materials, with a mass fraction of 5% Mn and the remainder being Zn, the proportioned raw materials were heated and melted in a graphite crucible. After holding the melt at 500°C for 10 minutes, it was poured into an alumina mold for cooling. The bottom of the alumina mold was a pure copper plate cooled by circulating water at 10°C. The melt was in direct contact with the pure copper plate and cooled rapidly at a cooling rate of 780 K / min. After cooling, a cast Zn-5Mn alloy was obtained, which is referred to as Invention Example 1.

[0037] The material of Example 1 of the invention has the following six characteristics:

[0038] (1) From MnZn 13 The structure consists of three phases: Mn, Zn9, and Zn. The following will discuss MnZn... 13Together with MnZn9, they are collectively referred to as Zn-Mn intermetallic compounds;

[0039] (2) The volume fraction of the Zn-Mn intermetallic compound phase is 77%, and the volume fraction of the Zn phase is 23%;

[0040] (3) MnZn 13 It forms a Zn-Mn core / shell structure with MnZn9, where the core is MnZn9 and the shell is MnZn. 13 This Zn-Mn core / shell structure is granular with an average size of 30 μm;

[0041] (4) In the Zn-Mn core / shell structure, MnZn 13 The shell can be either closed or open.

[0042] (5) A Zn phase is continuously distributed between the Zn-Mn core / shell structured particles, see Figure 1 ;

[0043] (6) The Zn-Mn core / shell structured particles have good deformability. When the Zn-Mn alloy is subjected to 50% compressive strain, the Zn-Mn core / shell structured particles elongate along a direction at 45° to the pressure direction without undergoing penetrating fracture. See Figure 2 .

[0044] The compressive mechanical properties were tested according to the national standard GB / T 7314-2017 "Metallic Materials - Compression Test at Room Temperature".

[0045] The material described in Example 1 of the invention has the following properties:

[0046] (1) The compressive mechanical properties at room temperature are a yield strength of 247 MPa, and no cracks appear when the strain reaches 80%. At this point, the stress reaches 2640 MPa. The compressive stress-strain curve is shown below. Figure 3 As shown, Zn-5Mn(FC) is the first invention example;

[0047] (2) Hardness is 130HV;

[0048] (3) In an aqueous solution containing 3% KCl at 93℃, the degradation rate was 0.1 mg / (cm³). 2 ·h);

[0049] (4) In an aqueous solution containing 3% KCl at 93℃, a wear ball made of zirconia ceramic with a diameter of 10 mm was used to apply a force of 5 N and wear at a frequency of 60 Hz for 1 h, and the average depth of the wear track was 3 μm.

[0050] (5) The antibacterial rate against Escherichia coli is 90%, and the antibacterial rate against Staphylococcus aureus is 92%.

[0051] Example 2: A ductile Zn-Mn alloy with a core-shell structure volume fraction of 60%

[0052] Using pure Zn and pure Mn as raw materials, with a mass fraction of 4% Mn and the remainder being Zn, the proportioned raw materials were heated and melted in a graphite crucible. After holding the melt at 600°C for 5 minutes, it was poured into a zirconia mold for cooling. The bottom of the zirconia mold was a pure silver plate cooled with ethanol at -20°C. The melt was in direct contact with the pure silver plate and cooled rapidly at a cooling rate of 850 K / min. After cooling, a cast Zn-4Mn alloy was obtained, which is referred to as Invention Example 2.

[0053] The microstructure of the as-cast material of Example 2 has the following five characteristics:

[0054] (1) From MnZn 13 The structure consists of three phases: Mn, Zn9, and Zn. The following will discuss MnZn... 13 Together with MnZn9, they are collectively referred to as Zn-Mn intermetallic compounds;

[0055] (2) The volume fraction of the Zn-Mn intermetallic compound phase is 60%, and the volume fraction of the Zn phase is 40%.

[0056] (3) MnZn 13 It forms a Zn-Mn core / shell structure with MnZn9, where the core is MnZn9 and the shell is MnZn. 13 This Zn-Mn core / shell structure is granular with an average size of 20 μm;

[0057] (4) In the Zn-Mn core / shell structure, MnZn 13 The shell can be either closed or open.

[0058] (5) The Zn phase is continuously distributed between the Zn-Mn core / shell structure particles.

[0059] The compressive mechanical properties were tested according to the national standard GB / T 7314-2017 "Metallic Materials - Compression Test at Room Temperature".

[0060] The as-cast material of Example 2 has the following properties:

[0061] (1) The room temperature compressive mechanical properties are a yield strength of 235 MPa and no cracks appear when the strain reaches 80%;

[0062] (2) Hardness is 125HV;

[0063] (3) In an aqueous solution containing 3% KCl at 93℃, the degradation rate was 0.09 mg / (cm³). 2 ·h);

[0064] (4) In an aqueous solution containing 3% KCl at 93℃, a wear ball made of zirconia ceramic with a diameter of 10 mm was used to apply a force of 5 N and wear at a frequency of 60 Hz for 1 h, and the wear depth was 3.5 μm.

[0065] (5) The antibacterial rate against Escherichia coli is 92%, and the antibacterial rate against Staphylococcus aureus is 93%.

[0066] Furthermore, the as-cast material of Invention Example 2 is rolled into shape with the following process parameters: the temperature of the first pass is 380°C and the reduction rate is 40%; the temperature of the second pass is 300°C and the reduction rate is 30%; the temperature of the third pass is room temperature and the reduction rate is 10%; thus, Invention Example 2 sheet with good surface quality is obtained.

[0067] The as-cast material of Invention Example 2 was extruded and formed with the following process parameters: 350°C and extrusion ratio of 100:1, resulting in the bar of Invention Example 2, which has good surface quality and no cracks.

[0068] The tensile mechanical properties were tested according to the national standard GB / T 7314-2017 "Metallic Materials - Compression Test at Room Temperature".

[0069] The room temperature tensile mechanical properties of the plate are as follows: yield strength is 260 MPa, tensile strength is 310 MPa, and elongation is 20%; it has good anti-aging ability, and after being placed at room temperature for 1 year, the strength change is 3.5%, which is not significant.

[0070] The room temperature tensile mechanical properties of the bar are as follows: yield strength 290 MPa, tensile strength 350 MPa, elongation 15%; it has good anti-aging ability, and after being placed at room temperature for 1 year, the strength change is 3%, with no significant difference.

[0071] Example 3: A ductile Zn-Mn alloy with a core-shell structure volume fraction of 90%

[0072] Using pure Zn and pure Mn as raw materials, with a mass fraction of 5.7% Mn and the remainder being Zn, the proportioned raw materials were heated and melted in a graphite crucible. After holding the melt at 500°C for 10 minutes, it was poured into an alumina mold for cooling. The bottom of the alumina mold was a graphite plate cooled by circulating water at 15°C. The melt was in direct contact with the graphite plate and cooled rapidly at a cooling rate of 780 K / min. After cooling, a cast Zn-5.7Mn alloy was obtained, which is referred to as Invention Example 3.

[0073] The microstructure of the as-cast material of Example 3 has the following characteristics:

[0074] (1) From MnZn 13 The structure consists of three phases: Mn, Zn9, and Zn. The following will discuss MnZn... 13Together with MnZn9, they are collectively referred to as Zn-Mn intermetallic compounds;

[0075] (2) The volume fraction of the Zn-Mn intermetallic compound phase is 90%, and the volume fraction of the Zn phase is 10%.

[0076] (3) MnZn 13 It forms a Zn-Mn core / shell structure with MnZn9, where the core is MnZn9 and the shell is MnZn. 13 This Zn-Mn core / shell structure is granular with an average size of 40 μm;

[0077] (4) In the Zn-Mn core / shell structure, MnZn 13 The shell can be either closed or open.

[0078] (5) The Zn phase is continuously distributed between the Zn-Mn core / shell structure particles.

[0079] The compressive mechanical properties were tested according to the national standard GB / T 7314-2017 "Metallic Materials - Compression Test at Room Temperature".

[0080] The as-cast material of Example 3 has the following properties:

[0081] (1) The room temperature compressive mechanical properties are a yield strength of 260 MPa and no cracks appear when the strain reaches 55%;

[0082] (2) Hardness is 140HV;

[0083] (3) In an aqueous solution containing 3% KCl at 93℃, the degradation rate was 0.12 mg / (cm³). 2 ·h);

[0084] (4) In an aqueous solution containing 3% KCl at 93℃, a wear ball made of zirconia ceramic with a diameter of 10 mm was used to apply a force of 5 N and wear at a frequency of 60 Hz for 1 h, and the wear depth was 2 μm.

[0085] (5) The antibacterial rate against Escherichia coli is 85%, and the antibacterial rate against Staphylococcus aureus is 88%.

[0086] Furthermore, the as-cast material of Invention Example 3 was rolled into shape with the following process parameters: the temperature of the first pass was 380°C and the reduction rate was 25%; the temperature of the second pass was 300°C and the reduction rate was 20%; the temperature of the third to sixth passes was 200°C and the reduction rate was 15%; thus, Invention Example 3 sheet with good surface quality was obtained.

[0087] The as-cast material of Invention Example 3 was extruded and formed with the following process parameters: 200°C and extrusion ratio of 8:1, resulting in the rod material of Invention Example 3, which has good surface quality and no cracks.

[0088] The tensile mechanical properties were tested according to the national standard GB / T 7314-2017 "Metallic Materials - Compression Test at Room Temperature".

[0089] The room temperature tensile mechanical properties of the plate are as follows: yield strength is 280 MPa, tensile strength is 325 MPa, and elongation is 15%; it has good anti-aging ability, and after being placed at room temperature for 1 year, the strength change is 2%, with no significant difference.

[0090] The room temperature tensile mechanical properties of the bar are as follows: yield strength 300 MPa, tensile strength 370 MPa, elongation 12%; it has good anti-aging ability, and after being placed at room temperature for 1 year, the strength change is 3%, with no significant difference.

[0091] Comparative Example 1: MnZn 13 Brittle Zn-Mn alloy with a volume fraction of 77%

[0092] Pure Zn and pure Mn were used as raw materials, with 5% Mn and the remainder Zn as the proportion of raw materials. The proportioned raw materials were heated and melted in a graphite crucible. The melt was held at 500℃ for 10 minutes and then poured into an alumina mold for cooling at a cooling rate of 12K / min. After cooling, a cast Zn-5Mn alloy was obtained, which was designated as Comparative Example 1.

[0093] The microstructure of the material in Comparative Example 1 has the following three characteristics:

[0094] (1) From MnZn 13 The composition of the two phases, Zn and Zn, is significantly different from that of Invention Example 1;

[0095] (2) The corresponding Zn-Mn intermetallic compound phase (i.e., MnZn) 13 The volume fraction of the phase was 77%, and the volume fraction of the Zn phase was 23%.

[0096] (3) MnZn 13 The phases are connected in large sections, with discontinuous Zn phases distributed within them, which is significantly different from the continuous Zn phase in Example 1 of the invention.

[0097] The performance testing method is the same as that of Example 1. The material of Comparative Example 1 was found to have the following properties: room temperature compressive mechanical properties, yield strength of 263 MPa, fracture at 10% strain, and fracture stress below 400 MPa; its corresponding compressive stress-strain curve is also... Figure 3 In the text, it is labeled as Zn-5Mn(AC). A comparison shows that Invention Example 1 and Comparative Example 1 have the same Mn content, but the compressive strength of Invention Example 1 is at least twice that of Comparative Example 1.

[0098] Comparative Example 1 crumbled into pieces during rolling and extrusion, making it impossible to roll or extrude into shape. Therefore, the plasticity and processability of Comparative Example 1 are far lower than those of Invention Example 1. Since Comparative Example 1 cannot be rolled into sheet or extruded into bar, the mechanical properties of the sheet or bar of Comparative Example 1 cannot be measured.

[0099] Comparative Example 2: MnZn 13 Brittle Zn-Mn alloy with a volume fraction of 60%

[0100] Pure Zn and pure Mn were used as raw materials, with 4% Mn and the remainder Zn as the proportion of raw materials. The proportioned raw materials were heated and melted in a graphite crucible. After the melt was held at 600℃ for 5 minutes, it was poured into a zirconia mold for cooling at a cooling rate of 8K / min. After cooling, a cast Zn-4Mn alloy was obtained, which was designated as Comparative Example 2.

[0101] The microstructure of the material in Comparative Example 2 has the following three characteristics:

[0102] (1) From MnZn 13 The composition of these two phases, Zn and Zn, is significantly different from that of Invention Example 2;

[0103] (2) The corresponding Zn-Mn intermetallic compound phase (i.e., MnZn) 13 The volume fraction of the phase is 60%, and the volume fraction of the Zn phase is 40%.

[0104] (3) MnZn 13 The phases are connected in large sections, with discontinuous Zn phases distributed within them, which is significantly different from the continuous Zn phases in Example 2 of the invention.

[0105] The performance testing method was the same as that of Invention Example 2. The material of Comparative Example 2 was found to have the following properties: it fractured at room temperature compressive strain of 12%; it crumbled into fragments during rolling and extrusion, and could not be rolled or extruded. Therefore, Comparative Example 2 has the same Mn content as Invention Example 2, but its plasticity and processability are far lower than those of Invention Example 2. Since Comparative Example 2 cannot be rolled into a sheet or extruded into a bar, the mechanical properties of the sheet or bar of Comparative Example 2 could not be measured.

[0106] Comparative Example 3: MnZn 13 Brittle Zn-Mn alloy with a volume fraction of 90%

[0107] Pure Zn and pure Mn were used as raw materials, with Mn accounting for 5.7% by mass and the balance being Zn. The prepared raw materials were heated and melted in a graphite crucible. The melt was held at 500℃ for 10 minutes and then poured into an alumina mold for cooling at a cooling rate of 12K / min. After cooling, a cast Zn-5.7Mn alloy was obtained, which was designated as Comparative Example 3.

[0108] The microstructure of the material in Comparative Example 3 has the following three characteristics:

[0109] (1) From MnZn 13 The composition of the two phases, Zn and Zn, is significantly different from that of Invention Example 3;

[0110] (2) The corresponding Zn-Mn intermetallic compound phase (i.e., MnZn) 13 The volume fraction of the phase is 90%, and the volume fraction of the Zn phase is 10%.

[0111] (3) MnZn 13 The phases are connected in large sections, with discontinuous Zn phases distributed within them, which is significantly different from the continuous Zn phases in Example 3 of the invention.

[0112] The performance testing method was the same as that of Example 3 of the Invention. The material of Comparative Example 3 was found to have the following properties: it fractured at room temperature compressive strain of 10%; it crumbled into fragments during rolling and extrusion, and could not be rolled or extruded into shape. Therefore, Comparative Example 3 has the same Mn content as Example 3 of the Invention, but its plasticity and processability are far lower than those of Example 3 of the Invention. Since Comparative Example 3 cannot be rolled into a sheet or extruded into a bar, the mechanical properties of the sheet or bar of Comparative Example 3 could not be measured.

[0113] Comparative Example 4: Rapidly Cooled Pure Zn

[0114] Pure Zn was heated and melted in a graphite crucible. The melt was held at 500°C for 10 minutes and then poured into an alumina mold for cooling. The bottom of the alumina mold was a pure copper plate cooled by circulating water at 10°C. The melt was in direct contact with the pure copper plate and cooled rapidly at a rate of 780 K / min. After cooling, a cast pure Zn material was obtained, which is referred to as Comparative Example 4.

[0115] The material in Comparative Example 4 has the following properties:

[0116] (1) The room temperature compressive yield strength is 103 MPa, which is only 44% of that of Example 1;

[0117] (2) The hardness is 45HV, which is only 35% of that of Example 1;

[0118] (3) In an aqueous solution containing 3% KCl at 93°C, a wear ball made of zirconia ceramic with a diameter of 10 mm was used to apply a force of 5 N and wear at a frequency of 60 Hz for 1 hour. The average depth of the wear mark was 7 μm, which is 2.3 times that of Example 1.

[0119] Therefore, it can be seen that in Examples 1 to 3 of the invention, the addition of Mn improves the material properties.

Claims

1. A method for preparing a high-strength, high-ductility Zn-Mn alloy with a core-shell structure, characterized in that, Using pure Zn and pure Mn as raw materials, with a mass fraction of 4.0-5.7% Mn and the remainder being Zn, the proportioned raw materials are heated and melted in a graphite crucible. The melt is held at 500-600℃ for 5-10 minutes and then poured into a mold made of a material with low thermal conductivity to cool. The bottom of the mold is a base plate made of a material with high thermal conductivity, which is continuously cooled by a liquid with a temperature below 20℃. After the melt enters the mold, it comes into direct contact with the base plate and is rapidly cooled at a rate greater than 750 K / min. Upon complete solidification, the Zn-Mn alloy is obtained. The Zn-Mn alloy is composed of Mn and Zn. 13 The structure consists of three phases: MnZn9 and Zn. 13 Together with MnZn9, they are collectively referred to as Zn-Mn intermetallic compounds; The MnZn 13 It forms a Zn-Mn core / shell structure with MnZn9, where the core is MnZn9 and the shell is MnZn. 13 This Zn-Mn core / shell structure is granular with an average size ≤40μm.

2. The method for preparing the high-strength, high-ductility Zn-Mn alloy with a core-shell structure as described in claim 1, characterized in that, The material with low thermal conductivity is alumina or zirconium oxide; the material with high thermal conductivity is pure copper, pure silver, aluminum alloy, AlN, or graphite; the liquid is water or ethanol.

3. The method for preparing the high-strength, high-ductility Zn-Mn alloy with a core-shell structure as described in claim 1, characterized in that, The volume fraction of the Zn-Mn intermetallic compound phase is ≥60%, and the volume fraction of the Zn phase is 10% to 40%.

4. The Zn-Mn core / shell structure as described in claim 1, characterized in that, In the Zn-Mn core / shell structure, MnZn 13 The shell has a closed or open structure.

5. The method for preparing the high-strength, high-ductility Zn-Mn alloy with a core-shell structure as described in claim 1, characterized in that, The Zn phase is continuously distributed between the Zn-Mn core / shell structured particles.

6. The method for preparing the high-strength, high-ductility Zn-Mn alloy with a core-shell structure as described in claim 1, characterized in that, The Zn-Mn alloy can be plastically formed by rolling or extrusion to produce plates and bars of various sizes; the rolling process is: room temperature to 380°C, with a single-pass reduction rate of 5% to 40%; the extrusion process is: 200 to 350°C, with an extrusion ratio of 8:1 to 100:1; the resulting plates and bars have no cracks on the surface and good processability.

7. The method for preparing the high-strength, high-ductility Zn-Mn alloy with a core-shell structure as described in claim 1, characterized in that, The as-cast state has the following properties: (1) The room temperature compressive mechanical properties are a yield strength greater than 230 MPa and no cracks appearing when the strain is greater than 50%, exhibiting very high plasticity; (2) Hardness greater than 120HV; (3) In an aqueous solution containing 3% KCl at 93℃, the weight loss rate is greater than 0.08 mg / (cm³). 2 ·h); (4) In an aqueous solution containing 3% KCl at 93℃, a wear ball made of zirconia ceramic with a diameter of 10 mm was used to apply a force of 5 N and wear at a frequency of 60 Hz for 1 h, and the wear depth was less than 4 μm. (5) It has antibacterial properties, with antibacterial rates of ≥85% against Staphylococcus aureus and Escherichia coli.

8. The method for preparing the high-strength, high-ductility Zn-Mn alloy with a core-shell structure as described in claim 6, characterized in that, The room temperature tensile mechanical properties of the plate and bar of the high-strength and high-plasticity Zn-Mn alloy with core-shell structure are as follows: yield strength greater than 250 MPa, tensile strength greater than 300 MPa, elongation greater than 10%; it has good anti-aging ability, and after being placed at room temperature for 1 year, the strength change is within 5%, with no significant difference.

9. The application of the high-strength, high-ductility Zn-Mn alloy with a core-shell structure prepared by the method according to claim 1 or 6, characterized in that, The Zn-Mn alloy can be used to manufacture oil extraction tools, automotive parts, stove valve bodies, roller skate brackets, hardware handrails, medical equipment housings, bone nails or bone plates.

Citation Information

Patent Citations

  • High-strength hot-dip galvanized steel sheet

    CN103857821A

  • High-plasticity and biodegradable Zn-Mn-system zinc alloy and preparation method thereof

    CN107177754A